2022
DOI: 10.1097/jsm.0000000000001019
|View full text |Cite
|
Sign up to set email alerts
|

Elite Athletes Successfully Return to the Preinjury Level of Sport Following Ankle Syndesmosis Injuries: A Systematic Review and Meta-Analysis

Abstract: Objective:To comprehensively review and report the outcomes of ankle syndesmotic injury management in elite athletes.Data sources:Three databases were searched for articles reporting the rate of return to sport following treatment of ankle syndesmotic injuries in elite athletes (collegiate or professional level). Ten articles and 440 athletes were included. Articles reporting the rate of return to sport following high ankle sprain injury in elite athletes. Data collected included demographics, type of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…50,52,58 Nonoperative management is generally considered an appropriate treatment strategy for patients with a stable syndesmosis. 53,55,59 However, multiple degrees of variation exist within nonoperative management of such injuries, including the weight-bearing regimen and immobilization options, with reported lengths of immobilization ranging from 1 to 6 weeks. 53 A survey of orthopaedic surgeons in 2022 identified common surgical indications for syndesmotic fixation to include radiographic evidence of syndesmotic widening > 2 mm, findings of an AITFL injury with a concomitant PITFL or deltoid ligament injury on MRI, or diastasis of the distal tibiofibular joint at arthroscopy.…”
Section: Syndesmotic Fixationmentioning
confidence: 99%
See 4 more Smart Citations
“…50,52,58 Nonoperative management is generally considered an appropriate treatment strategy for patients with a stable syndesmosis. 53,55,59 However, multiple degrees of variation exist within nonoperative management of such injuries, including the weight-bearing regimen and immobilization options, with reported lengths of immobilization ranging from 1 to 6 weeks. 53 A survey of orthopaedic surgeons in 2022 identified common surgical indications for syndesmotic fixation to include radiographic evidence of syndesmotic widening > 2 mm, findings of an AITFL injury with a concomitant PITFL or deltoid ligament injury on MRI, or diastasis of the distal tibiofibular joint at arthroscopy.…”
Section: Syndesmotic Fixationmentioning
confidence: 99%
“…55,60,61 Suture button constructs have also been reported to have lower rates of complications and obviate the need for routine removal. 55,59,60 Among a survey of orthopaedic surgeons, dynamic fixation with suture button constructs was the preferred fixation approach for syndesmotic injuries. 52 Previous studies demonstrated high rates of American Orthopedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot scores, a validated instrument evaluating patient outcomes following an ankle or hindfoot injury.…”
Section: Syndesmotic Fixationmentioning
confidence: 99%
See 3 more Smart Citations